Comparison Testing Functional and Usability System Mapping Land Agriculture On Platform Web and Mobile - Chrismanto, Antonius Rachmat; Purwadi, Joko; Wibowo, Argo; Santoso, Halim Budi; Delima, Rosa; Balisa, Delfia (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2021)
The Agricultural Land Mapping System (SPLP) is indispensable in an agricultural country where part of the population is farmers. This system has been developed by the research team since 2019 and has resulted in web and mobile based systems. The Dutatani SPLP system was developed using the Rapid Application Development (RAD) method. Before this system is further implemented in the community, this system needs to be tested in terms of functionality and usability. This research article aims to compare the functionality and reusability testing of web and mobile-based SPLP. The test was carried out using ISO / IEC 9126-4 usability metrics that focus on effectiveness and efficiency, and involve farmers and farmer groups from Gilang Harjo Village, Bantul, Yogyakarta. The results of testing the web-based and mobile-based SPLP system show that overall respondents can do all the tasks given, but it takes a long time to complete. This is influenced by internal factors of the respondents, namely the respondent's lack of experience in using mobile phones for other activities besides telephone and short messages. So that when testing, respondents need more time to adapt to the system. However, based on time on task, mobile-based SPLP testing is faster than web-based ones.